1990
DOI: 10.1021/ja00176a049
|View full text |Cite
|
Sign up to set email alerts
|

The effect on MLCT excited states of electronic delocalization in the acceptor ligand

Abstract: 1991 photochemistry, radiation chemistry, chemoluminescence photochemistry, radiation chemistry, chemoluminescence O 0160 -094Effect on MLCT Excited States of Electronic Delocalization in the Acceptor Ligand.-Metal to ligand charge transfer (MLCT) excited states of (Ru(bpy))2+ ( bpy: 2,2'-bipyridyl) and related complexes are utilized as sensitizers of photochemical electron transfer. To circumvent limitations of these complexes (decrease of lifetimes of the excited states with increase of the wavelength of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 0 publications
7
64
0
2
Order By: Relevance
“…[2] The bulky monocyclic [3] methylaluminum bis(4-bromo-2,6-di-tert-butylphenoxide) (MABR) also gives a clean reaction but with the opposite stereochemical preference, as defined by Yamamoto and co-workers. [4] As in Yamamotos work, the configuration of products 2 and 3 was confirmed by reduction; in our case OH-directed stereospecific addition of H 2 with Crabtrees catalyst [5] gave 4 and 5, respectively (Scheme 1).…”
Section: Methodssupporting
confidence: 74%
“…[2] The bulky monocyclic [3] methylaluminum bis(4-bromo-2,6-di-tert-butylphenoxide) (MABR) also gives a clean reaction but with the opposite stereochemical preference, as defined by Yamamoto and co-workers. [4] As in Yamamotos work, the configuration of products 2 and 3 was confirmed by reduction; in our case OH-directed stereospecific addition of H 2 with Crabtrees catalyst [5] gave 4 and 5, respectively (Scheme 1).…”
Section: Methodssupporting
confidence: 74%
“…[3] The protracted triplet lifetime can be explained within the framework of the energy-gap law in terms of residence of the promoted electron in an extended p* orbital that encompasses much of the bridging ligand. [4] Enlargement of the LUMO lowers the triplet energy, and thereby curtails mixing with higher-energy, metal-centered excited states. [5] In attempting to exploit this effect further we have found that the acetylene residue must be attached directly to the coordinated terpyridine ligand while the polyacetylenic bridge cannot comprise more than four ethynylene groups.…”
Section: Fine-tuning the Electronic Properties Of Binuclear Bis(terpymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Such prolonged triplet lifetimes have been recorded both in fluid solution at ambient temperature and in frozen glasses and for complexes formed from either 2,2′-bipyridine 1-4 or 2,2′:6′,2′′-terpyridine ligands. [5][6][7][8] Closely-related effects have also been observed 2,9 for the corresponding binuclear osmium(II) and rhenium(I) polypyridine complexes.…”
Section: Introductionmentioning
confidence: 97%